The Southward spread of Johannesburg and its impact on precolonial stone walled structures - Naidu, Saireeni Latisha (My University, 2018)
There are thousands of Stone Walled Structures (SWS) located in the southern half of the Gauteng Province. In the absence of relevant historical documents, these SWS are all the information we have about how pre-colonial societies were organized in this area. Unfortunately, they are threatened by rapid urbanization and development. This research attempts to estimate how many Iron Age SWS have been lost to urban development in Johannesburg South during the last 80 years. I mapped and quantified the SWS and urbanization in four chronological snapshots using remote sensing techniques. Aerial photographs from 1937 and 1961 were used as well as Google Earth satellite images from 2005 and 2015. The data was analyzed on the ESRI software ArcGIS 10.3. The four snapshots show the trend in urban sprawl and destruction of SWS and this information is valuable for mitigation strategies. Fortunately, there are legislations and procedures in place to ensure that not all these sites are lost forever.
Thesis (M.Sc.)--University of the Witwatersrand, Faculty of Science, School of Geography, Archaeology and Environmental Studies, 2018.
Keywords: Stone Walled Structures; Southern Johannesburg; Heritage Management; Remote Sensing; GIS; Stone age--South Africa; Stone walls--South Africa.; Archaeology--South Africa